Analisis Kemacetan Jalan Tol Lingkar Luar Jakarta (JOOR) Ruas S (Pondok Pinang-Taman Mini) Jakarta - Mardianto, Hendrik; Tjahjani, Indra (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The JORR S toll road is part of the JORR toll road which runs around the city of Jakarta starting from Penjaringan and ending in Tanjung Priok. The JORR toll road is an important transportation artery to facilitate the flow of logistics distribution and mobility of the people of Jakarta and its surroundings. On observation of JORR S toll road congestion often occurs most of the day.This research was conducted on the JORR toll road section S starting from Pondok Pinang, South Jakarta (KM 19+800) to Taman Mini East Jakarta (KM 32+800). The data used as material for the research is traffic data for February 2023 obtained from the JORR S toll road BUJT, namely PT. Hutama Karya Branch Jorr S. Performance analysis of JORR S toll road section using Indonesian Road Capacity Manual 1997. Analyze the relationship between speed, density, and traffic flow using the Greenshield method. Analysis of travel time affected by shock waves in the toll entrance merging area. The results of the analysis of the degree of saturation of the JORR S toll road section more than 1 (service level F) occur on line A at 14.00 – 19.00 and on line B at 07.00 – 18.00, saturation degree 0.85 – 1 on line A occurs at 07.00 – 14.00, 19.00 – 20.00, on line B occurs at 06.00 – 07.00, 18.00 – 20.00. this indicates that the condition of the JORR S toll road section is poor. The congestion that occurs on the JORR S toll road section is caused by traffic flow that almost or even exceeds the capacity of the existing road. Traffic flow on lines A and B is dominated by light vehicles (LV) with a percentage of 84.80% on line A and 82.27% on line B. The average travel time during peak hours is 06.00 – 21.00 on line A 65.65 minutes and line B 173.70 minutes.